1. Limited time only! Sign up for a free 30min personal tutor trial with Chegg Tutors
    Dismiss Notice
Dismiss Notice
Join Physics Forums Today!
The friendliest, high quality science and math community on the planet! Everyone who loves science is here!

Homework Help: Dx/dt = x(t)(1-x(t))

  1. Jan 16, 2013 #1
    1. The problem statement, all variables and given/known data

    Where am I going wrong in solving this differential equation?

    2. Relevant equations

    x' = x(1-x) is what I'm after

    3. The attempt at a solution

    Separating variables: dx / [x(1-x)] = dt
    Partial fraction decomposition on the left side yields: dx [1/x + 1/(1-x)] = dt.
    Integrating both sides with respect to their variable: ln(x) + ln(1-x) = t + C
    Simplifying the left side: ln(x(1-x)) = t + C
    Raising both sides to the e power: x(1-x)=Ket

    Nothing I can really do after this, though. I guess I just define it implicitly like that?
  2. jcsd
  3. Jan 16, 2013 #2
    Another question:

    Any idea how I can get a formula for the x for which cos(x)=ex?
  4. Jan 17, 2013 #3


    Staff: Mentor

    Your mistake is just above.
    $$ \int \frac{dx}{1 - x} \neq ln(1 - x)$$

  5. Jan 17, 2013 #4


    User Avatar
    Science Advisor
    Homework Helper

    Also, if you get x(1 - x) = f(t) you can definitely solve for x -- if you look more closely it's just a quadratic equation.
    First correct the error pointed out by Mark though :)

    As for your other question cos(x) = ex does not have an algebraic solution.
  6. Jan 17, 2013 #5
    Ok. Because one of our hw questions was to solve x'(t) = et - cos(t). Someone asked the professor what to do about the fact that there are infinitely many fixed points, and he told us to just deal with x'(0)=0 but to explain how we know there are infinitely many other solutions.
  7. Jan 17, 2013 #6
    Ah, I see. :smile:

    So then we have

    x' = x(1-x)
    ---> dx / [x(1-x)] = dt
    ---> dx/x + dx/(1-x) = dt
    ---> ln(x) - ln(1-x) = t + c
    ---> ln[x/(1-x)] = t + c
    ---> x/(1-x) = Cet
    ---> (1-x)/x = Ke-t
    ---> 1/x - 1 = Ke-t
    ---> 1/x = 1 + Ke-t
    ---> x(t) = 1/(1+Ke-t)
    ---> x(0) = 1(1+K), K = x(0)-1
    ---> x(t) = 1/[1+(X(0)-1)e-t]
  8. Jan 17, 2013 #7


    User Avatar
    Science Advisor

    One way to show it has more than one solution is to show a graph of [itex]y= cos(x)- e^x[/itex] and note that it crosses the x-axis multiple times.
Share this great discussion with others via Reddit, Google+, Twitter, or Facebook